Definition of a pool of epitopes that recapitulates the T cell reactivity against major house dust mite allergens. Issue 10 (15th September 2015) - Hinz, D.; Oseroff, C.; Pham, J.; Sidney, J.; Peters, B.; Sette, A.
Summary: Background: Allergens from house dust mites (HDM) are a common cause of asthma. Der p and Der f from Dermatophagoides sp . are strong immunogens in humans. Allergen extracts are used to study T helper (Th2) cell responses to HDM, which are implicated in the development and regulation of allergic disease. Objective: To define an epitope mixture that recapitulates, and might substitute for, HDM extract in terms of detecting and characterizing Th2 cell responses. Methods: Peripheral blood mononuclear cells (PBMC) from 52 HDM allergic and 10 non‐allergic individuals were stimulated with HDM extracts and assayed with a set of 178 peptides spanning mite allergens group Der p 1, 2, 23 and Der f group 1 and 2 allergens. A pool of the most dominant T cell epitopes identified in the present study and from published literature was assembled and tested for ex vivo T cell responses. Correlation with HDM‐specific IgE titres was examined. Results: Patterns of T cell reactivity to Der p and Der f – derived peptides revealed a large number of epitopes. Clear patterns of immunodominance were apparent, with HDM allergen group 1 and 2 dominant over group 23. Furthermore, within a given antigen, 6–11 epitopes accounted for the vast majority of responses. Based on these results and published data, a comprehensive dust mite pool (DMP) of epitopes was designed and found to allow detection of ex vivo T cell responses. DMP ex vivo reactivity correlated with HDM‐specific IgE titres and was similar to that detected with commonly used HDM extracts. Ex vivo DMP stimulation was associated with a predominant Th2 response in allergic donors, and minor reactivity of T cells producing IFNÎ³, IL17 and IL10. Conclusions & Clinical Relevance: A detailed map of Der p and Der f antigens defined a pool of epitopes that can be used to detect ex vivo HDM responses.